Komunikasi Visual Untuk Memudahkan Pasien Dan Pengunjung Mencari Informasi Di Rumah Sakit Muhammmadiyah Palembang - Satya Dzakirah (Jurnal Aksi Dosen dan Mahasiswa, 2025)
Hospitals are complex healthcare facilities with various service units, so patients and visitors often have difficulty finding the information they need. Visual communication plays an important role in facilitating access to information through effective and easy-to-understand designs. This study aims to design a visual communication system that can help patients and visitors find locations, understand service procedures, and access important information more quickly and efficiently at the Muhammadiyah Hospital in Palembang. The methods used in this study include direct observation, interviews with hospital staff, and user needs analysis. The results of the study indicate that the use of visual elements such as wayfinding maps, clear iconography, contrasting colors, and readable typography can enhance the effectiveness of information communication in hospitals. With the implementation of a well-designed visual communication system, patients and visitors can become more independent in seeking information, reduce confusion, and improve the overall healthcare experience.